Strengthening the Socio-Economic Potential of Teluk Latak Village as an Independent Village on the Coast of Bengkalis Island - Reni Suryanita; Yohannes Firzal; Geovani Meiwanda; Yosi Alwinda; Harnedi Maizir (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Teluk Latak Village is located in Bengkalis District, Bengkalis Regency. It has two hamlets, namely Langgam Muara Hamlet and Simpang Baru Hamlet. Teluk Latak Village is one of the coastal villages in the west of Bengkalis Island. This village has a flat topography with an area of approximately 23 km2 or about 4.47% of the entire area of Bengkalis District. Teluk Latak village is 14 km from the centre of government in Bengkalis District. Teluk Latak village has agricultural areas, plantations, and livestock. Teluk Latak village produces goats, native chickens and manila ducks. Like coastal areas, Teluk Latak Village is a fishing village. Teluk Latak Village can be developed based on the coastal village's existing social and economic conditions. Abrasion worries the people of Bengkalis, especially for people who live in the north of the island facing the Malacca Strait. This abrasion caused the oil palm plantations and rubber plantations to collapse one by one by the waves. This community service activity aims to assist village officials and the community in mapping the social and economic potential of Teluk Latak Village so that it can be realized as an independent village on the coast of Bengkalis Island. One of the activities is counselling on preventing coastal damage and managing marine fishery products into nutritious snacks consumed by fishers' families who have an excess fish catch. Teluk Latak Village people can develop snacks made from processed fish to improve the household economy. It is hoped that this activity can contribute to village residents and village officials in mapping the potential of Teluk Latak Village in the social and economic fields